ANALISA PENILAIAN KONDISI IRIGASI RAWA TELANG I KABUPATEN BANYUASIN - Baniva, Ratih; Sinta Devi, Debby (Jurnal Tekno Global, 2024)
ABSTRACT  Irrigation is defined as the process of providing a controlled supply of water to agricultural land through a specially designed distribution system. The Telang I area has unique hydrological conditions as it is surrounded by several major rivers such as the Musi River, Banyuasin River and Telang River. Good irrigation management supports water conservation, uses resources sustainably and reduces environmental impacts. Irrigation condition analysis is an assessment and improvement plan for irrigation infrastructure to ensure long-term functionality. This study aims to determine the irrigation condition of Rawa Telang I in Muara Telang Sub-district, Banyuasin Regency. The methodology used includes field surveys, interviews with farmers and irrigation managers, as well as condition analysis and maintenance recommendations. The results of the research from the analysis of the condition of the channels and supporting buildings obtained maintenance recommendations. The results of the research from the analysis of channel conditions and supporting buildings obtained maintenance recommendations. Maintenance on primary channels, namely 3 channels carried out routine maintenance and 2 channels periodic maintenance. In the maintenance of secondary channels, 21 channels are carried out routine maintenance, 86 channels are carried out periodic maintenance and 11 channels are rehabilitated. Supporting buildings, namely 3 regulating buildings and 2 protective embankments are carried out periodic maintenance. The conclusion of this research is the need for maintenance measures tailored to the current conditions so that both channels and buildings pendung irrigation Rawa Telang I can function optimally and support the efficiency of water resources management. Keywords: Irrigation, Telang I, Condition Analysis   ABSTRAK Irigasi didefinisikan sebagai proses penyediaan suplai air yang terkontrol ke lahan pertanian melalui sistem distribusi yang dirancang secara khusus. Daerah Telang I memiliki kondisi hidrologi yang unik karena dikelilingi oleh beberapa sungai besar seperti Sungai Musi, Sungai Banyuasin dan Sungai Telang. Pengelolaan irigasi yang baik mendukung konservasi air, menggunakan sumber daya secara berkelanjutan dan mengurangi dampak lingkungan. Analisis kondisi irigasi berupa penilaian dan rencana perbaikan infrastruktur irigasi untuk memastikan fungsionalitas jangka panjang. Penelitian ini bertujuan untuk mengetahui bagaimana kondisi irigasi Rawa Telang I di Kecamatan Muara Telang, Kabupaten Banyuasin. Metodologi yang digunakan meliputi survei lapangan, wawancara dengan petani dan pengelola irigasi, serta analisis kondisi dan rekomendasi pemeliharaan. Hasil penelitian dari analisis kondisi saluran dan bangunan penunjang diperoleh rekomendasi pemeliharaan. Pemeliharaan pada saluran primer, yaitu 3 saluran dilakukan pemeliharaan rutin dan 2 saluran pemeliharaan berkala. Pada pemeliharaan saluran sekunder yaitu 21 saluran dilakukan pemeliharaan rutin, 86 saluran dilakukan pemeliharaan berkala dan 11 saluran dilakukan rehabilitasi. Bangunan pendukung yaitu 3 bangunan pengatur dan 2 tanggul pelindung dilakukan pemeliharaan berkala. Kesimpulan dari penelitian ini adalah perlunya tindakan pemeliharaan yang disesuaikan dengan kondisi saat ini sehingga baik saluran maupun bangunan pendung irigasi Rawa Telang I dapat berfungsi dengan optimal dan mendukung efisiensi pengelolaan sumber daya air. Kata Kunci : Irigasi, Telang I, Analisis Kondisi